2018
DOI: 10.1109/tns.2017.2765481
|View full text |Cite
|
Sign up to set email alerts
|

Total Ionizing Dose Effects on a Radiation-Hardened CMOS Image Sensor Demonstrator for ITER Remote Handling

Abstract: Abstract-Total Ionizing Dose (TID) effects are studied on a radiation hardened by design (RHBD) 256x256-pixel CMOS image sensor (CIS) demonstrator developed for ITER remote handling by using X and γ-rays irradiations. The (color) imaging capabilities of the RHBD CIS are demonstrated up to 10 MGy(SiO2), 1 Grad(SiO2), validating the radiation hardness of most of the designed integrated circuit. No significant sensitivity (i.e. responsivity and color filter transmittance) or readout noise degradation is observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Conversely, when the TID level increase above 5 kGy(SiO 2 ) the image lag degradation affects all the studied pixels design due to the deep potential pocket in the PPD-TG edge. In this case 4T PPD pixels are not suitable and 3T-pixels with conventional photodiodes [16]- [19] have to be preferred. Indeed, they allow the use of RHBD solutions such as drawing a ring of polysilicon (or P+ doping) around the photodiode.…”
Section: B Improvement Solutionsmentioning
confidence: 99%
“…Conversely, when the TID level increase above 5 kGy(SiO 2 ) the image lag degradation affects all the studied pixels design due to the deep potential pocket in the PPD-TG edge. In this case 4T PPD pixels are not suitable and 3T-pixels with conventional photodiodes [16]- [19] have to be preferred. Indeed, they allow the use of RHBD solutions such as drawing a ring of polysilicon (or P+ doping) around the photodiode.…”
Section: B Improvement Solutionsmentioning
confidence: 99%
“…Previous works have demonstrated not only that reaching a 10 MGy (1 Grad) radiation hardness with a CIS is feasible [2], [3], but also that a full camera composed of the FUsion for energy Radiation Hard Image sensor (FURHI) [4] and Imaging System (FURHIS) [5] demonstrators can be made radiation hard up to several MGy(SiO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is indeed known that the readout chain of a CIS 3.3 V P channel transistors exhibit very high threshold voltage (V th ) shift (about 500 mV) at TID beyond 100 kGy because of large gate oxide trapped charge induced V th shifts, whereas 3.3 V N-channel transistors V th is slightly influenced by interface state induced shift [2]. In order to mitigate the P-MOSFETs sensitivity, two different ways of improvement have been proposed: the first, explored in [3] consists in designing a full 1.8V CIS to limit the use of double gate oxides; the second one, which has been selected for the FURHI project, is to base the analog design only on 3.3 V N channel transistors [4]. The FURHI CIS characterization has revealed new imager performance degradation sources due the V th MOSFETs variability.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available off-the-shelf radiation tolerant cameras based on solid-state image sensors, such as charge injection devices or CIS, are limited to a maximum total ionizing dose (TID) of 100 kGy(SiO 2 ) [4], [5]. Goiffon et al [6] has demonstrated that optimized radiation-hardened CISs can withstand TID up to 10 MGy(SiO 2 ). It has been shown thatradiation-hardening-by-design (RHBD) solutions such as the use of 1.8-V nMOSFET and pMOSFET or the exclusive use of N transistors for CIS readout chain reduce the threshold voltage shift induced by TID, thus improving the dynamics of the sensors itself.…”
mentioning
confidence: 99%
“…It has been shown thatradiation-hardening-by-design (RHBD) solutions such as the use of 1.8-V nMOSFET and pMOSFET or the exclusive use of N transistors for CIS readout chain reduce the threshold voltage shift induced by TID, thus improving the dynamics of the sensors itself. Moreover, optimized pixel design architectures have been proposed to reduce the dark current increase with radiation dose [6].…”
mentioning
confidence: 99%